Impact of surgical margin status on the survival outcome after surgical resection of gastric cancer: a protocol for systematic review and meta-analysis. Issue 11 (4th November 2020) - Jiang, Zhiyuan; Cai, Zhaolun; Yin, Yuan; Shen, Chaoyong; Huang, Jinming; Yin, Yiqiong; Zhang, Bo
Abstract : Introduction: Generally, complete resection with cancer cell negative (R0) margin has been accepted as the most effective treatment of gastric cancer and positive resection (R1/R2) margin has been associated with decreased survival to varied degrees. However, the independent impact of microscopical positive (R1) margin on long-term survival may be confounded. No meta-analysis has worked at the association between R1 margin and outcomes of gastric cancer and the available evidence are scant. Therefore, we plan to conduct a systematic review and meta-analysis to quantitatively explore the role of R1 margin on gastric (including oesophagogastric junction) cancer survival after curative intent resection. Methods and analysis: The protocol was conducted according to Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols guideline. A systematic search of PubMed, Embase and the Cochrane Central Register of Controlled Trials databases will be performed from their inceptions to 30 April 2020 to identify randomised controlled trials (RCTs), cohort studies and case–control studies focusing on the impact of R1 margin on survival of gastric cancer after curative intent resection. The primary outcome will be the overall survival (OS) and disease-free survival (DFS) and the secondary outcomes will be 5-year OS rate and 5-year DFS rate. The Cochrane tool for bias assessment in randomised trials and Risk Of Bias In Non-randomised Studies-I for the assessment of bias in non-randomised studies (NRS) will be used. Statistical heterogeneity will be assessed by visual inspection of forest plots and measured using the I 2 statistics. A fixed-effect model will be used when heterogeneity is low, otherwise, a random-effect model will be chosen. Publication bias will be assessed by funnel plots, subgroup analysis and sensitivity analysis will be performed in the right context. For each outcome, we will perform data synthesis separately for RCTs and NRS using Rev Man V.5.3 software and compile 'summary of findings' tables separately for RCTs and NRS using GRADEpro software. Grading of Recommendations, Assessment, Development and Evaluations considerations will also be used to make an overall assessment of the quality of evidence. Ethics and dissemination: There is no requirement for ethics approval because no patient data will be collected at an individual level in this systematic review and meta-analysis. The results of this systematic review will be published in a peer-reviewed journal and presented at relevant conferences, any deviations from the protocol will be clearly documented and explained in its final report. PROSPERO registration number: CRD42020165110.